2020
DOI: 10.1177/1066480720925829
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Parenting and the Moderating Impact of Gender and Single-Parent Family Structure on Self-Efficacy and Well-Being

Abstract: The intersection of helicopter parenting, gender, and single-parent family on self-efficacy and well-being is examined. Existing research on helicopter parenting focuses on negative consequences. Using a sample of students at a university in the mid-southern United States ( N = 247), we find that helicopter parenting is negatively related to self-efficacy and well-being for emerging adult sons from single-parent family backgrounds. Previous research suggests a negative relationship of divorce on sons. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Third, greater efforts are needed to include important demographic, social, and cultural factors to better understand their influences, rather than treating them merely as control variables and covariates and trivializing their effects. For example, the findings from the current review suggested that gender of emerging adult children and parents could play an important (moderating) role in the association between overparenting and emerging adult development (e.g., Buchanan & LeMoyne, 2020a, 2020bLove et al, 2020;. Using a more gender-balanced sample would allow a closer look into the potential main and interactive gender effects.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 84%
See 1 more Smart Citation
“…Third, greater efforts are needed to include important demographic, social, and cultural factors to better understand their influences, rather than treating them merely as control variables and covariates and trivializing their effects. For example, the findings from the current review suggested that gender of emerging adult children and parents could play an important (moderating) role in the association between overparenting and emerging adult development (e.g., Buchanan & LeMoyne, 2020a, 2020bLove et al, 2020;. Using a more gender-balanced sample would allow a closer look into the potential main and interactive gender effects.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 84%
“…Eighteen studies further examined mediating mechanisms between overparenting and psychological well-being, with frequently studied cognitive mediators such as basic psychological needs satisfaction (e.g., Carr et al, 2021; Schiffrin et al, 2014; Schiffrin, Erchull, et al, 2019), self-control (e.g., Hong & Cui, 2020; Kwon et al, 2015; Wang et al, 2021), and self-efficacy (e.g., Love, Cui, Allen, et al, 2020). Several studies examining moderating mechanisms identified the unique role of gender of emerging adults and/or parents (e.g., Buchanan & LeMoyne, 2020a, 2020b; Kouros et al, 2016; Love et al, 2020; Rousseau & Scharf, 2015; Schiffrin et al, 2019) and family structure (e.g., Buchanan & LeMoyne, 2020b). The main findings of overparenting and emerging adults’ psychological outcomes are almost in complete agreement except for one study with mixed findings.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these concerns, Finley, Mira, and Schwartz (2008) emphasize the use of self-report measures as valid, especially with emerging adults who may be freer to report on their parents than younger children. Additionally, several studies have found that other parenting variables, such as helicopter parenting (e.g., Buchanan & LeMoyne, 2020a;Buchanan & LeMoyne, 2020b;Patock-Peckham & Morgan-Lopez, 2009), may further influence the development of self-esteem in emerging adulthood, and it was not assessed in the current study.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…Supportive parenting with appropriate autonomy granting is a defining characteristic of authoritative parenting. Alternatively, overprotective or helicopter parenting (i.e., overinvolved parenting) limits developmentally appropriate autonomy granting, and has negative outcomes for male and female EACS (Buchanan & LeMoyne, 2020a, 2020bPatock-Peckham & Morgan-Lopez, 2009). However, females from single-parent households with a low autonomy granting parent may not experience similar negative effects on self-efficacy as their male counterparts (Buchanan & LeMoyne, 2020a).…”
Section: Parenting Styles and Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation